2023
DOI: 10.3390/gels9070522
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Emulsifier Addition on the Functionalization of a High-Oleic Palm Oil-Based Oleogel

Abstract: Alternatives to oils with high saturated fatty acid content are often liquid oils (high in unsaturated fatty acids) that have a modified structure created either through additives or processing. Emulsifiers are additives that can be used as structuring agents of liquid fats; this process results in products such as oleogels, which can broaden the applications of these oils. This study assessed and compared the effects of mono- and diglycerides at 3%, 5%, 7% and 10% w/w on the mechanical and thermal properties … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 41 publications
0
0
0
Order By: Relevance
“…These results were consistent with the findings of Mozzon et al [12], who also showed that 'hybrid palm oil' had an oleic acid content higher than crude palm oil. The thermal transitions are aligned with results for HOPO in [8,25]. Based on the onset temperature and peak crystallization points observed in both oils, the mechanical, rheological, and visual characteristics were tested at 20 While most of the work in this study focused on temperatures above 0 °C (in the common range of food industry applications), the first large melting peak for HOPO had an onset of −5.45 °C which ends at 3.5 °C, while for SPO, the peak extends up to 10 °C.…”
Section: Differential Scanning Calorimetrymentioning
confidence: 72%
See 1 more Smart Citation
“…These results were consistent with the findings of Mozzon et al [12], who also showed that 'hybrid palm oil' had an oleic acid content higher than crude palm oil. The thermal transitions are aligned with results for HOPO in [8,25]. Based on the onset temperature and peak crystallization points observed in both oils, the mechanical, rheological, and visual characteristics were tested at 20 While most of the work in this study focused on temperatures above 0 °C (in the common range of food industry applications), the first large melting peak for HOPO had an onset of −5.45 °C which ends at 3.5 °C, while for SPO, the peak extends up to 10 °C.…”
Section: Differential Scanning Calorimetrymentioning
confidence: 72%
“…Currently, there is limited knowledge on the crystallization kinetics and physical properties of HOPO and its products [24]. Publications have addressed the use of HOPO in oleogel formulations using mono and diglycerides [25] and some of these oleogels perform identically to SPO oleogels in the baking of cookies [26]. However, a general characterization of HOPO is needed to understand this oil as an ingredient and enable the expansion of its use to multiple applications.…”
Section: Introductionmentioning
confidence: 99%